Architecture as affective law enforcement: theorising the Japanese koban - Young, Alison (Crime, media, culture, 2022)
Criminology has long understood architecture to be both a problem, in that design might increase the pains of an individual’s experience within the criminal justice system, and its solution. Study of the Japanese koban, or police box, reveals the ways in which the architecture and design of a built form communicate the values and objectives of criminal justice. The article draws upon recent criminological thinking about space and about the senses, in which the materiality of public space is understood to have a powerfully affective dimension, and in which meaning arises through the signifying practices of places, events and experiences. In Japan, police boxes have a lengthy history as an architectural manifestation of a mode of policing designed to surveill, reassure, and monitor. Extensive and immersive research conducted in Japan during a 2-year period investigated the ways in which koban both ‘take place’, as built forms within public spaces, and also ‘make sense’, as signifying practice designed to communicate the values and intentions of Japanese community policing and an ‘affective atmosphere’ of law enforcement.